Beneficial effects of cooling during constant power non-steady state cycling - Homestead, E. P.; Ryan, B. J.; Goodrich, J. A.; Byrnes, W. C. (International Journal of Sports Medicine, 2017)
This study compared the effects of cooling on the energetic and associated physiological and perceptual responses to constant power, non-steady state cycling. Twelve males cycled at their lactate threshold power for 60 min or until exhaustion under 3 conditions: wearing a cooling vest and sleeves (COOL), a synthetic shirt embedded with an active particle technology claimed to facilitate evaporative heat loss (EVAP), and a standard synthetic shirt (CON). When adjusted for time, the increase in gastrointestinal temperature from baseline was reduced during COOL and EVAP compared to CON (1.44±0.45 and 1.52±0.43 vs. 1.66±0.45°C, p<0.05). Sweat rate was reduced during COOL compared to EVAP and CON (1 12±331 vs. 1 525±393 and 1 550±548 mL/h, p<0.01). Gross efficiency decreased over time across conditions (p<0.01), but COOL attenuated this decrease by 22% compared to CON (p<0.05). The rating of perceived exertion was reduced during COOL and EVAP compared to CON (p<0.01). In conclusion, cooling using a vest and sleeves or wearing an active particle technology shirt reduced the rise in gastrointestinal temperature and rating of perceived exertion compared to a standard synthetic shirt. Cooling using a vest and sleeves also reduced the decrease in gross efficiency and sweat rate compared to wearing the standard synthetic shirt.